Da “servidão dos juros” à “colônia de banqueiros”: uma análise dos escritos de Gottfried Feder e Gustavo Barroso - Lima, Marcelo Alves de Paula (Temporalidades, 2014)
Buscamos estabelecer diálogos entre os escritos de dois importantes ideólogos: um nazista, Gottfried Feder, e outro integralista, Gustavo Barroso. Notamos, em ambos os autores, a defesa da moralização da economia e um chamado à luta contra as altas finanças internacionais, associadas ao judeu. O tema da opressão dos bancos e dos juros é mobilizado de forma bastante similar nas duas obras. Diferente, porém, de Barroso, Feder defendia um projeto engajado no expansionismo imperialista e no desenvolvimento industrial.ABSTRACT: We sought to establish dialogues between the writings of two distinguished ideologue: a nazi, Gottfried Feder, and an integralist one, Gustavo Barroso. Both authors call for the moralization of the economy and for the struggle against the international high finances, which are linked to the Jewish people. The theme of the oppression from banks and interests is mobilized in a very similar way in the two books. Unlike Barroso, however, Feder stood up for a project that was engaged on the imperialist expansion and the industrial development.KEYWORDS: national-socialism, integralism, anti-imperialism.